24-hour electrocardiographic study of heart rate and rhythm patterns in population of healthy children. Issue 3 (March 1981) - Southall, D P; Johnston, F; Shinebourne, E A; Johnston, P G
Abstract : Twenty-four hour electrocardiographic recordings were made on 104 randomly selected, healthy 7 to 11-year-old children. Ninety-two were technically adequate and suitable for analysis. The mean highest heart rate measured by direct electrocardiographic analysis over nine beats was 164 +/- 17. The mean lowest heart rates were 49 +/- 6 over three beats', and 56 +/- 6 over nine beats' duration. The maximum duration of heart rates less than 55/minute was 40 minutes. At their lowest heart rates 41 children (45 per cent) had junctional escape rhythms, the maximum duration of which was 25 minutes. Nine children showed PR intervals greater than or equal to 0.20 s and included three with Mobitz type I second degree atrioventricular block. Nineteen (21%) had isolated supraventricular or ventricular premature beats (less than 1/hour). Sixty subjects (65%) had sinus pauses that could not be distinguished on the surface electrocardiogram from those previously described as sinuatrial exit block or sinus arrest. The maximum duration of sinus pause measured over 24 hours on each child was 1.36 +/- 0.23 seconds. Thus apparently healthy children show variations in heart rate and rhythm over 24 hours hitherto considered to be abnormal.